Water marks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Searching for Equity. Conceptions of justice and equity in peasant irrigation. Edited by R Boelens and G Davila. 1998. 473 pp. ISBN 90 232 3385 9. NLG 49.50 van Gorcum publishers PO Box 43 NL 9400 AA Assen The Netherlands. Fax: +31 592 37